1993
DOI: 10.1080/07315724.1993.10718355
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary medium- and long-chain triglycerides on fat deposition and lipogenic enzyme activities in rats.

Abstract: The present study investigates fat deposition, variances of fatty acid (FA) composition, and lipogenic enzyme activities through dietary medium- and long-chain triglyceride (MCT and LCT) supplementation in growing rats. Eighteen male Wistar rats were divided into three groups and fed isocalorically for 4 weeks with control (based on AIN 76), MCT (C8:0 26%), or LCT (corn oil 25%) diets. Compared to the control group with 0.28 +/- 0.01, feed efficiency was lower in the MCT rats and greater in the LCT rats (0.24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…This corroborates a previous finding in rats, that described that WAT accumulates more in MCFA than control diet fed animals, despite no difference in body mass [5]. However a contradictory finding in a rat study demonstrated that epididymal mass was similar in animals fed control diet or medium chain triglyceride-rich diets, compared to enlarged epididymal fat mass in animals fed long chain triglycerides [31]. We found no observable GPR84 genotype-specific effect on body fat accumulation, suggesting that differences in epididymal fat accumulation are not dependent on GPR84.…”
Section: Discussionsupporting
confidence: 85%
“…This corroborates a previous finding in rats, that described that WAT accumulates more in MCFA than control diet fed animals, despite no difference in body mass [5]. However a contradictory finding in a rat study demonstrated that epididymal mass was similar in animals fed control diet or medium chain triglyceride-rich diets, compared to enlarged epididymal fat mass in animals fed long chain triglycerides [31]. We found no observable GPR84 genotype-specific effect on body fat accumulation, suggesting that differences in epididymal fat accumulation are not dependent on GPR84.…”
Section: Discussionsupporting
confidence: 85%
“…Conversely, Takase and Hosoya reported that three days of a diet containing MCT (probably with the same amount of MCFA as in our study) caused an enhancement of fatty acid synthase and malic enzyme, which was related with fatty acid lipogenesis similar to fatty acid synthase in Wistar rat livers (20). Similar results have been reported by other investigators (21)(22)(23)(24). These results indicated that (excess) MCFA could enhance lipogenic activity under certain condition, and our results suggested that the coexistence of LCFA decreased the lipogenic activity of MCFA.…”
Section: Effect Of Mcfa On Hepatic Enzyme Activity In Ratssupporting
confidence: 80%
“…Other reports have indicated the ability of MCT to enhance de novo lipogenesis in the liver. [35][36][37][38] It is thought that the magnitude of the enhancement in lipogenesis by MCFA might be one reason for the inconsistency in demonstrating a body fat-lowering effect of MCT. Its effect appears to depend on experimental conditions and the characteristics of subjects.…”
Section: Discussionmentioning
confidence: 99%